Ethnicity, domination and tyranny: A Case for the Ndebele people in Running with Mother (2012) (Journal for Studies in Humanities and Social Sciences, 2015)
Hegemonic state grand narratives are often absolutist in ways in which they insist on particular ways of viewing the past, present and the trajectory to the future. They canalize society’s attention to certain ways of remembering, forgetting and viewing the socio-political, economic, cultural and ethnic relations in ways that legitimate the state as quintessential. Zimbabwean history, in its patriotic sense, is appropriated by the state in order to inscribe technologies of domination and tyranny in politics and ethnicity. In this research we argue that contesting narratives like Running with Mother use memory and re-memory to establish patterns of marginalisation, violence and hegemony used by the ZANU-PF government. Mlalazi’s narrative uses memory of the Gukurahundi violence in order to confront ethnic and political injustices in the past and present and, in this way, seek justice and healing in the public sphere. We argue that ZANU-PF politics since 1980 has been totalitarian and geared towards the elimination of ZAPU and the Ndebele through various exclusions and coercive acts whose consequences have left the Ndebele confronted with the question of: Who are we (the minority) and what are the opportunities in an increasingly ‘Shonaised’ (ZANUFIED?) Zimbabwe? We conclude by arguing that violence was used by the ruling party on the Ndebele not to create an inclusive society but to establish ethnic domination and tyranny which is still manifest to this day. The act of remembering the violence therefore, becomes a site for psycho-social therapy in a situation where the dehumanization is unacknowledged, diminished or perpetuated in other guises.